(untitled) (Revista Argentina de Musicología, 2024)
In recent decades, the concept of cosmopolitanism has acquired considerable relevance in different areas of knowledge, which is reflected in a profuse multidisciplinary bibliography. In the theoretical discussion, this notion is far from a consensus, partly due to the different ideological and disciplinary perspectives at play. The aim here is to explore some of these perspectives in order to reflect on a significant repertoire of situations in twentieth-century Latin American classical music, in which the tensions between belonging and exclusion are manifested, in relation both to local traditions and to international languages.